Ovarian Hyperstimulation Syndrome as an Etiology of Obstructive Uropathy - Creticus P. Marak; Amit Chopra; Narendrakumar Alappan; Ana M. Ponea; Achuta K. Guddati (Case Reports in Obstetrics and Gynecology)
Ovarian hyperstimulation syndrome (OHSS) is an iatrogenic complication of controlled ovarian hyperstimulation (COH) protocols performed in women undergoing assisted reproductive technologies. Overstimulation of the ovaries results in the overproduction of vasoactive cytokines and mediators by the ovaries, thereby causing a generalized capillary leak and acute shift of protein-rich fluid from the intravascular compartment into the third space. This may lead to the development of ascites, pleural effusions, pericardial effusion, anasarca, intravascular volume depletion, hemoconcentration, oliguria, hypoalbuminemia and hypoproteinemia, electrolyte imbalances, acute renal failure, abdominal compartment syndrome, thromboembolic events, and adult respiratory distress syndrome. The only effective treatment available is prevention of the syndrome from developing by individualizing the stimulation protocol, especially in high-risk patients. Once the syndrome develops, the management is mainly supportive. Oliguria and some degree of acute renal failure commonly develop in patients with moderate to severe OHSS and are usually due to prerenal causes. Acute renal failure (ARF) secondary to obstructive uropathy is rare. Here we report a case of severe, life-threatening OHSS resulting in ARF secondary to obstructive uropathy.